Personalized Medicine: Bridging the Gap between Genetics and Clinical Practice (Asian Journal of Pharmaceutics (AJP), 2024)
Personalized medicine is a groundbreaking approach to healthcare that tailors’ treatment each patient based ontheir unique genetic makeup, environment, and lifestyle. A key part of this approach is pharmacogenomics, whichlooks at how genetic differences can affect and how patients respond to medications. By understanding howgenes influence drug metabolism and effectiveness, clinicians can choose the best medications and dosages forindividual patients, potentially improving treatment outcomes and minimizing side effects. This review delves intothe current landscape of personalized medicine and explores how pharmacogenomics plays a role in drug response,the opportunities and challenges of bringing personalized medicine into mainstream healthcare, and where thisinnovative field is headed in the future. Although personalized medicine has made great strides, challengesstill exist, including ethical issues, questions around cost-effectiveness, and the need for clear guidelines. Yet,with continued investment in research and addressing these hurdles, personalized medicine has the potential tosignificantly improve patient outcomes and transform the way healthcare is delivered.